TO‘QIMACHILIK SANOATI XOM ASHYOSI VA MAHSULOTLARI ISHLAB CHIQARILISHI GEOGRAFIK JIHATLARI - Ro‘zmetov, D.R. (SCIENCE and SOCIETY, 2024)
The article provides a brief description of the main types of raw materials of the textile industry, the volume of production and type composition in the world, as well as the geography of production and export.